Neural correlates of successful and partial inhibitions in children: an ERP study. - Cragg, L; Fox, A; Nation, K; Reid, C; Anderson, M (2009)
This experiment used event-related potentials (ERPs) to investigate the neural processes underlying the development of response inhibition in a modified version of the go/no-go paradigm [Cragg and Nation [2008] Developmental Science 11(6): 819-827]. N2 and P3 ERP components on correct go trials and partial and successful inhibitions were compared in 7- and 9-year-old children. A larger N2 effect on successful inhibitions was found in 9-year-olds compared to 7-year-olds at fronto-central electrodes. N2 amplitude was positively related to behavioral performance in the 7-year-olds suggesting it may reflect inhibitory processes; however, this relationship was not present in the 9-year-olds. Age differences were also apparent in the go P3, perhaps indicating differences in stimulus processing. The no-go P3 component was larger on successful than partial inhibitions. In contrast, there was no difference in N2 amplitude between partial and successful inhibitions. A significant difference was found in N2 latency however. This suggests that inhibitory processes are similar in both cases but initiated earlier on successful inhibitions. N2 latency was also shorter in 9-year-olds than 7-year-olds supporting an increase in the efficiency of response inhibition with age.